A New Fluorogenic Probe for the Detection of endo‐β‐N‐Acetylglucosaminidase. (16th February 2018) - Ishii, Nozomi; Sunaga, Chie; Sano, Kanae; Huang, Chengcheng; Iino, Kenta; Matsuzaki, Yuji; Suzuki, Tadashi; Matsuo, Ichiro
Abstract: We developed a fluorescence‐quenching‐based assay system to determine the hydrolysis activity of endo ‐β‐ N ‐acetylglucosaminidases (ENGases). The pentasaccharide derivative1 was labeled with an N ‐methylanthraniloyl group as a reporter dye at the non‐reducing end and with a 2, 4‐dinitrophenyl group as a quencher molecule at the reducing end. This derivative is hydrolyzed by ENGase, resulting in an increase in fluorescence intensity. Thus, the fluorescence signal is directly proportional to the amount of the tetrasaccharide derivative, hence allowing ENGase activity to be evaluated easily and quantitatively. Using this system, we succeeded in measuring the hydrolysis activities of ENGases and thus the inhibitory activities of known inhibitors. We confirmed that this assay system is suitable for high‐throughput screening for potential inhibitors of human ENGase that might serve as therapeutic agents for the treatment of N ‐glycanase 1 ( NGLY1 ) deficiency. Abstract : Real‐time monitoring of ENGase activity : A fluorescence‐quenching‐based assay system to determine the hydrolysis activity of endo ‐β‐ N ‐acetylglucosaminidase (ENGase) was developed. We succeeded in measuring the hydrolysis activities of ENGases quantitatively. This assay system is suitable for screening potential inhibitors of human ENGase, which could serve as therapeutic agents for N ‐glycanase 1 ( NGLY1 ) deficiency.